Dancing around the well : the circulation of commonplaces in Renaissance humanism - MacPhail, Eric (Brill's studies in intellectual history ;, 2014)
This study examines the transmission and transformation of commonplace wisdom in Renaissance humanism by tracing a series of filiations between classical sayings, anecdotes, and exampes and Renaissance poems, essays, and fictions. The circulation of commonplaces can be understood either as a process of reanimation and revitalization, where frozen sayings thaw out and come to life, or conversely as a process of immobilization and incrustation that petrifies tradition. The paradigmatic figure for this process is the proverbial dance around the well, which expresses both the danger and the compulsion of borrowed speech.